Influenza Vaccination Is Associated With Lower Incidental Asthma Risk in Patients With Atopic Dermatitis: A Nationwide Cohort Study - Li, Kun Hong; Leong, Pui-Ying; Tseng, Chung-Fang; Wang, Yu Hsun; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Background Atopic march refers to the natural history of atopic dermatitis (AD) in infancy followed by subsequent allergic rhinitis and asthma in later life. Respiratory viruses interact with allergic sensitization to promote recurrent wheezing and the development of asthma. We aimed to evaluate whether influenza vaccination reduces asthma risk in people with AD. Methods This cohort study was conducted retrospectively from 2000 to 2013 by the National Health Insurance Research Database (NHIRD). Patients with newly diagnosed AD (International Classification of Diseases, Ninth Revision, Clinical Modification code 691) were enrolled as the AD cohort. We matched each vaccinated patient with one non-vaccinated patient according to age and sex. We observed each participant until their first asthma event, or the end of the study on December 31, 2013, whichever came first. Results Our analyses included 4,414 people with a mean age of 53 years. Of these, 43.8 were male. The incidence density of asthma was 12.6 per 1,000 person-years for vaccinated patients, and 15.1 per 1000 person-years for non-vaccinated patients. The adjusted hazard ratio (aHR) of asthma in the vaccinated cohort relative to the non-vaccinated cohort was 0.69 (95% CI = 0.55–0.87). Vaccinated patients had a lower cumulative incidence of asthma than unvaccinated patients. Vaccinated participants in all age and sex groups trended toward a lower risk of asthma. People will reduce more asthma risk when taking shots every year. Conclusion Influenza vaccination was associated with lower asthma risk in patients with AD.